Neonatal genetic metabolic disease entities ought to be included in tandem mass spectrometry screening in China - Yi-xiao GONG; Xiao-hong SONG; Juan XU; Jia-yue DU; Li-chun XIE (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To systematically retrieve and sort out the information on neonatal genetic metabolic disease entities included in tandem mass spectrometry (MS/MS) screening in some countries and to provide a reference for entity expansion in the screening on neonatal genetic metabolic diseases with MS/MS in China. Methods With literature analysis and expert consultation, we assessed the priority order of the neonatal genetic metabolic diseases to be included in screening with MS/MS using a comprehensive score. Results Totally 53 neonatal genetic metabolic diseases were identified with the practicability of to be screened with MS/MS; of which, 23, 16, and 14 were aminoacidopathies, organic acidemias and fatty amino acid metabolic diseases, respectively. The diseases with top ten comprehensive scores in descending order are isovaleric acidemia, glutaric acidemia type Ⅰ, medium-chain acyl-CoA dehydrogenase deficiency, maple syrup urine disease, homocystinuria, propionic acidemia, methyl malonic acidemia, phenylketonuria, citrullinemia type Ⅰ, and very long-chain acyl-CoA dehydrogenase deficiency. Conclusion Based on the study results, we recommend that the ten neonatal genetic metabolic diseases with higher comprehensive scores ought to be included in MS/MS screening and the subsequent disease entities for the screening could be adjusted timely according to screening detection outcomes and the incidences of neonatal genetic metabolic diseases.